Exploring how women entrepreneurs gain and maintain legitimate professional identities in the consultancy industry - Brookes, Sarah (2018)
This work explores how women entrepreneurs in the consultancy industry legitimise their professional identities by analysing their entrepreneurial narratives. Primary qualitative data was collected through narrative-style interviews and secondary data through an internet search for publicly available representations of the women’s professional identities i.e. company websites, blogs, social media. These data revealed four shared characteristics within the process of professional identity formation: (1) motivational drivers to meet personal, client and family needs, (2) social strategies of connecting or differentiating, (3) gender strategies to navigate female advantage and disadvantage, and (4) proof of claim strategies to showcase educational, client and employment success. Motivational drivers were located within individual internal definition of self, whereas strategies could be identified as external representations of self, visible when implemented as symbolic actions. Crafting narrative accounts of symbolic actions is shown to be a key factor in legitimising symbolic action, freezing success stories in time for current and future audiences to assess, respond and make further contributions to the narrative thread if desired. Stakeholder responses and in some cases, narrative contributions to these actions works to legitimise the resulting representation of professional identity. A process model is developed to illustrate these particular behaviours and to demonstrate the iterative nature of legitimising professional identity through an ongoing cycle of strategically implemented symbolic action. The findings clarify the legitimising strategies in use by the women including use of storytelling as a means of conveying experiences. Narrative within the interview are contrasted with publicly available narrative accounts of symbolic actions, revealing inconsistencies between internal experiences and external narrative accounts, particularly in terms of gender disadvantage.